2020
DOI: 10.1101/2020.01.07.897546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human papillomavirus 16 positive cervical cancer in Guatemala: The D2 and D3 sublineages differ in integration rate and age of diagnosis

Abstract: Human papillomavirus (HPV) 16 displays substantial sequence variation; four HPV16 lineages (A, B, C, D) have been described, as well as multiple sub-lineages. To identify molecular events associated with HPV16 carcinogenesis we evaluated viral variation, the integration of HPV16, and somatic mutation in 96 cervical cancer samples from Guatemala. A total of 64% (60/94) of the samples had integrated HPV16 sequences, and integration was associated with an earlier age of diagnosis (P=0.0007) and pre-menopausal dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…We, and others, have previously demonstrated that, among multiethnic populations, HPV-16 infections with lineage D and sublineage A4 variants confer increased risk for cervical infection persistence and lesion development (Berumen et al, 2001;Hildesheim et al, 2001;Mirabello et al, 2016;Sichero et al, 2007). Specific HPV-16 variants seem also to be associated with histopathological features of cervical tumors, where variants of sublineages A1-A3 are associated only to squamous cell carcinomas (SCC), and those of lineage D are associated with both SCC and adenocarcinomas (ADC), which are often more aggressive than SCC (Berumen et al, 2001;Lou et al, 2020;Mirabello et al, 2016). A summary of tumor vs. nontumor samples may be found in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We, and others, have previously demonstrated that, among multiethnic populations, HPV-16 infections with lineage D and sublineage A4 variants confer increased risk for cervical infection persistence and lesion development (Berumen et al, 2001;Hildesheim et al, 2001;Mirabello et al, 2016;Sichero et al, 2007). Specific HPV-16 variants seem also to be associated with histopathological features of cervical tumors, where variants of sublineages A1-A3 are associated only to squamous cell carcinomas (SCC), and those of lineage D are associated with both SCC and adenocarcinomas (ADC), which are often more aggressive than SCC (Berumen et al, 2001;Lou et al, 2020;Mirabello et al, 2016). A summary of tumor vs. nontumor samples may be found in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that HPV-16 lineage D variants are associated with a higher risk of infection persistence and cervical cancer development (Sichero et al, 2007;Xi et al, 2007;Mirabello et al, 2016) mostly within populations with a multiethnic composition. In addition, higher rates of integration are observed for lineage D variants compared to other HPV-16 variants (Lou et al, 2020). However, this relationship in male-associated anogenital cancers is, by far, less reported.…”
Section: Introductionmentioning
confidence: 99%